2009
DOI: 10.1002/ange.200905169
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric 6π Electrocyclization: Enantioselective Synthesis of Functionalized Indolines

Abstract: Scheme 1. Strategic approach to asymmetric electrocyclization.Scheme 2. Catalysts examined in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…Quenching of this anion with an appropriate electrophile would also give access to all-carbon quaternary stereocentres. Our previous investigations into the counterion-directed cyclization of delocalized anions to form indolines [17,18] and indolenines [19] has demonstrated that analogous transformations can proceed with high enantioselectivity.…”
mentioning
confidence: 99%
“…Quenching of this anion with an appropriate electrophile would also give access to all-carbon quaternary stereocentres. Our previous investigations into the counterion-directed cyclization of delocalized anions to form indolines [17,18] and indolenines [19] has demonstrated that analogous transformations can proceed with high enantioselectivity.…”
mentioning
confidence: 99%
“…Treatment of an in situ generated N-aryl imine 180 with K 2 CO 3 in the presence of catalyst 2 v afforded the cyclized product 181 in good yield and high enantioselectivity (Scheme 115). [150] Brire and co-workers reported the asymmetric [3+2] cycloaddition of allylic sulfone 182 and chalcone under phasetransfer conditions. The reaction was promoted by the simplified Maruoka catalyst (S)-4 a to give product 183 with moderate enantioselectivity (Scheme 116).…”
Section: Other Cyclizationsmentioning
confidence: 99%
“…Such strategies have been well documented, including a chiral synthon strategy, [5] metal catalysis, [6] and organocatalysis. [7] Despite these impressive advances, the development of a direct method for the synthesis of enantioenriched 2-substituted indolines continues to be highly desirable.…”
mentioning
confidence: 99%